Demographic transition patterns and their impact on the age structure - Chesnais, J. C.
tbls., gráfs.
pp. 327-336
Keywords: Transicion Demografica; Composicion de la Poblacion; Distribucion por Edad; Analisis Demografico; Jovenes; Ancianos